Effect of crosslinking agents on chitosan microspheres in controlled release of diclofenac sodium - Gonçalves,Vanessa L. (2005)
In this work chitosan microspheres were prepared by the simple coacervation method and crosslinked using epichlorhydrin or glutaraldehyde for the controlled release of diclofenac sodium. The effects of the crosslinking agents on chitosan microspheres over a 12-hour period were assessed with regard to swelling, hydrolysis, porosity, crosslinking, impregnation of diclofenac sodium (DS), and consequently to the release of DS in buffer solutions, simulating the gastrointestinal tract. The degree of swelling varied with the pH for glutaraldehyde chitosan microspheres (GCM) and epichlorhydrin chitosan microspheres (ECM). Partial acid and basic hydrolysis affected the swelling behavior of the GCM matrix. Release kinetics of diclofenac sodium from these matrices were investigated at pH 1.2, 6.8 and 9.0, simulating the gastrointestinal tract conditions. The results indicated that the release mechanism deviated slightly from Fickian transport.